Vom Verlierer zum Gewinner – und zurück: der Coal Miner als Schlüsselfigur der britischen Zeitgeschichte - Arnold, Jörg (Vandenhoeck & Ruprecht, 2016)
This article traces the cyclical trajectory of the British coal miner from the mid-1960s to the mid-1980s. Within less than one generation, the miner turned from doomed industrial proletarian to self-assured embodiment of the future back to doomed proletarian. The renaissance of King Coal in the 1970s proved short-lived, and yet it needs to be taken seriously if one is to understand the nature of the coal strike of 1984/85 and the rundown of the industry that followed. Indeed, the figure of the miner offers a lens for reconfiguring our understanding of the 1970s and British contemporary history more generally, as the article seeks to demonstrate both empirically and conceptually.